Efésios 5.21-33 como modelo de discurso de gênero - Guimarães, Simone Furquim (2011)
Violence is a recurring theme in Brazilian society. Its roots go back to antiquity and its effects remain, today, noticeable in the daily life of many women around the world. It is known that in Brazil every 15 seconds and 1 woman is assaulted, and this perverse statistics of women dying in their homes is still a taboo subject in many sectors of society. As the prospect of violence against women, the study of biblical and theological feminist cutting has produced relevant analysis regarding the socioreligious, and in dialogue with the sociological research has fostered new perspectives on the problem. Thus, the aim here is to probe the discursive discourse in drafting the text of Ephesians 5. 21-33, which contains specific directives for the conduct of the Christian woman, and assess how far such a policy is based on broad cultural movements of the context in which it was produced and their possible links with the later religious reality.